2019
DOI: 10.2147/cmar.s232073
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Novel Prognostic Scoring Model Based on Albumin and γ-Glutamyltransferase for Hepatocellular Carcinoma Prognosis</p>

Abstract: These authors contributed equally to this work Aim: To investigate the predictive value of albumin (ALB) and γ-glutamyltransferase (GGT) in hepatocellular carcinoma (HCC) patients undergoing curative resection. We sought to establish a new scoring model for predicting the prognosis of HCC patients undergoing curative resection. Patients and methods: A retrospective analysis was performed in 303 HCC patients who underwent curative resection. Preoperative risk factors for survival were investigated using univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 35 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…Moreover, AKP is also found to be correlated with epithelial mesenchymal transition phenotypes in HCC; epithelial mesenchymal transition is considered to be a major step in tumor invasion or metastasis [28,29]. Furthermore, ALB is conventionally considered as an indicator of nutritional status, and low levels of ALB indicate a dysfunction of protein synthesis in the liver [31], which may eventually impair immunity. In addition, emerging evidence has revealed that ALB can stabilize cell growth, exert antioxidant effects against carcinogens, and suppress tumor cell proliferation by reducing the phosphorylation of Rb proteins [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, AKP is also found to be correlated with epithelial mesenchymal transition phenotypes in HCC; epithelial mesenchymal transition is considered to be a major step in tumor invasion or metastasis [28,29]. Furthermore, ALB is conventionally considered as an indicator of nutritional status, and low levels of ALB indicate a dysfunction of protein synthesis in the liver [31], which may eventually impair immunity. In addition, emerging evidence has revealed that ALB can stabilize cell growth, exert antioxidant effects against carcinogens, and suppress tumor cell proliferation by reducing the phosphorylation of Rb proteins [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a recent increase in its consideration as a practical marker [19][20][21], especially for that group of almost 50% of HCC patients who do not have elevated AFP [22][23][24][25]. Furthermore, there have been several other reports of the usefulness of GGT in combination with other markers [26][27][28][29][30][31], as well as a metaanalysis [32]. Of particular note in our analysis, was the usefulness of combination GGT plus albumin in the low-AFP cohort, for whom there are few other validated tumor markers (Tables 11 and 12).…”
Section: Discussionmentioning
confidence: 99%
“…Peng et al found that ALB is a biomarker, which is related to the early diagnosis, metastasis, prognosis, or treatment of HCC [ 50 ]. The levels of ALB and GGT before operation are potential biomarkers to predict the prognosis of patients with liver cancer undergoing radical resection [ 51 ]. The evaluation of liver fibrosis degree is an important basis for the clinical diagnosis and treatment of HCC.…”
Section: Discussionmentioning
confidence: 99%